Human Health Risks Related to Penicillin G and Oxytetracycline Residues Intake Through Beef Consumption and Consumer Knowledge About Drug Residues in Maroua, Far North of Cameroon - Vougat Ngom, Ronald R. B.; Foyet, Harquin S.; Garabed, Rebecca; Zoli, André P. (Frontiers in Veterinary Science, 2020)
In Cameroon, a leading livestock production country, previous study highlighted the extensive misuse of veterinary drugs in the Far North Region where we found the second cattle population of the country. Based on former work describing the presence of penicillin G (PEN) and oxytetracycline (OTC) residues in beef sold for human consumption in Maroua, the capital city of the Far North Region, this study was designed to determinate the risk of PEN and OTC residues intake via beef consumption by the population of Maroua and to evaluate the consumer’s knowledge on drug residues. Dietary exposure determinate here was based on the average consumption of beef (found during a survey of 202 households randomly selected in Maroua) and the average concentration of the two antibiotic residues in beef (obtained after LC-MS/MS analysis of samples of liver and muscle collected from 202 cattle selected randomly in all the slaughterhouses of Maroua) found in our previous studies. The estimated daily intake per capita of OTC and PEN residues from beef consumption were 22.81 μg and 2.37 μg respectively. The risk was then assessed as high (9.6% range from 6.4 to 15.4% of acceptable daily intake (ADI)) and considerable (2.2% range from 1.5 to 3.5% of ADI) for PEN and OTC residues respectively. Based on the mean value it can be concluded that the estimated risk of antibiotic daily intake through beef in Maroua is high (5.9% of ADI). Also, 98% of the surveyed population are not aware that meat can be contaminated by residues of veterinary drugs administered to slaughter animals. This ignorance would also increase the risk of contamination of the population of Maroua with antibiotic residues. This work clearly highlights the high risk of consuming beef by the population of Maroua. Taking into consideration the evidence of the intake of antibiotic residues from others sources, it is therefore very imperative that measures be taken by the Government to ensure food safety in order to guarantee the health of the populations of this region in particular and Cameroon in general. Hence, the need for the establishment of a national food safety plan.